Pengaruh Pelatihan, Kompensasi Dan Motivasi Kerja Terhadap Prestasi Kerja Karyawan (Pada PT. Sang Bima Sakti Sidoarjo) - Denny Kurniawan; Hadi Sunaryo; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstrack Based on the research carried out with the aim of analyzing the influence of the influence of training, compensation and work motivation on employee performance at PT. Bima sakti Sidoarjo. The population in this study were employees of PT. Bima sakti, which numbered 52 people. The study uses a quantitative approach that is influential (regression). This study used a saturated sample because all members of the population were selected as samples, namely all employees of PT. Bima Sakti Sidoarjo totaling 52 employees. The analytical method used in this research is multiple linear regression analysis with hypothesis testing using t test and f test. From this research, the answers that have been previously processed show that simultaneously Job Training, Work Compensation and Work Motivation have an effect on Job Performance, Job Training has an effect on Work Performance, Work Compensation has an effect on Work Performance, and Work Motivation has an effect on Work Performance. Keywords: Job Training, Work Compensation, Work Motivation, Work Performance